Kelengkapan Imunisasi Dasar Pada Bayi Tergantung Pengetahuan Ibu - Ai Sapuroh; Andri Nur Sholihah (Politeknik Kesehatan Kementrian Kesehatan Semarang, 2023)
Immunization is the cornerstone of effective disease prevention in reducing mortality and morbidity in toddlers. Diseases that can be prevented by immunization, among others: Tuberculosis (TBC), Tetanus Diphtheria, Hepatitis B, Pertussis, Measles, Polio. This research was conducted to determine the correlation between mother's knowledge about basic immunization to the completeness of basic immunization in infants. The study employed a quantitative analytic survey method with a cross sectional approach. The data collection used a purposive sampling technique with a sample size of 50 respondents and data analysis used the chi square test. The results of the analysis found that there was a correlation between mother's knowledge and completeness of basic immunization (p=0.000). The mother's level of understanding is, thus, a factor in obtaining full basic immunization. As a result, it is indeed essential to provide the mother with information that will expand her knowledge. Additionally, health professionals can inform mothers about the benefits of immunization, post-immunization, and regarding immunization laws in Islam so that mothers believe that immunization has a good impact and mothers that behave towards immunization.